2022
DOI: 10.1186/s12943-022-01618-5
|View full text |Cite
|
Sign up to set email alerts
|

LINE-1 promotes tumorigenicity and exacerbates tumor progression via stimulating metabolism reprogramming in non-small cell lung cancer

Abstract: Background Long Interspersed Nuclear Element-1 (LINE-1, L1) is increasingly regarded as a genetic risk for lung cancer. Transcriptionally active LINE-1 forms a L1-gene chimeric transcript (LCTs), through somatic L1 retrotransposition (LRT) or L1 antisense promoter (L1-ASP) activation, to play an oncogenic role in cancer progression. Methods Here, we developed Retrotransposon-gene fusion estimation program (ReFuse), to identify and quantify LCTs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 92 publications
1
29
0
Order By: Relevance
“…Taken together, de-repression of repetitive elements may not be a barrier to transformation particularly when p53 and RB are co-deleted. Consistent with this notion is the observation in human cancers that the tumor suppressors p53 and RB are frequently co-mutated (31)(32)(33)(34)(35) and that these tumors often express high levels of repetitive elements, (25,(36)(37)(38). Furthermore, because retrotransposition of LINE-1 in human cancers can lead to large chromosomal deletions, translocations, and gene amplification (1) it is conceivable that suppression of repetitive elements by p53 and RB may be an important mechanism for tumor suppression.…”
Section: Elementsmentioning
confidence: 71%
“…Taken together, de-repression of repetitive elements may not be a barrier to transformation particularly when p53 and RB are co-deleted. Consistent with this notion is the observation in human cancers that the tumor suppressors p53 and RB are frequently co-mutated (31)(32)(33)(34)(35) and that these tumors often express high levels of repetitive elements, (25,(36)(37)(38). Furthermore, because retrotransposition of LINE-1 in human cancers can lead to large chromosomal deletions, translocations, and gene amplification (1) it is conceivable that suppression of repetitive elements by p53 and RB may be an important mechanism for tumor suppression.…”
Section: Elementsmentioning
confidence: 71%
“…NTRK contains NTRK1, NTRK2, and NTRK3, which respectively encode TRKA, TRKB, and TRKC (Koga et al, 2022;Manea et al, 2022). First-generation TRK inhibitors larotrectinib and entrectinib are currently the drugs of choice for patients with NTRK-fusion tumors (Liu et al, 2022;Manea et al, 2022). Solvent front mutations, such as G595R, G623R, and G667C, are the causes of the most common type of resistance.…”
Section: Target Drugs Clinically Used Drug Resistance Mechanismsmentioning
confidence: 99%
“…PTEN (phosphatase and tensin homolog), which was recently identified as a tumor suppressor gene with bispecific phosphatase activity, is also a gene that is second only to the P53 gene in its close relationship to carcinogenesis and plays an important role in cell proliferation, apoptosis, adhesion, migration, and infiltration (Liu et al, 2022;Fang et al, 2022). PTEN is frequently inactivated in various malignancies, such as brain, prostate, endometrial, gastric cancers and NSCLC, and clinical data have suggested that PTEN loss of function occurs in 10%-25% of NSCLC cases (Liu et al, 2022). To date, studies have indicated that PTEN loss of function mainly affects the PI3K/AKT pathway, thereby affecting cell proliferation, migration and other processes (Figure 2) (Cho et al, 2022).…”
Section: Ptenmentioning
confidence: 99%
See 2 more Smart Citations